Pengabdian kepada Masyarakat: Meningkatkan Aksesibilitas Pendidikan bagi Anak-Anak Kurang Mampu - Hamdanesti, Rischa (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Education is a key factor in improving the quality of human resources. However, accessibility to education for underprivileged children still faces various barriers, both economic, social, and geographical. This community service activity aims to provide an alternative solution to increase educational accessibility through learning assistance programs, the provision of supporting facilities, and the empowerment of parents to support their children's education. The method used is a participatory approach, where the community is actively involved in the planning, implementation, and evaluation of the activity. The results of the activity indicate an increase in children's learning motivation, the availability of simple learning resources, and increased parental awareness of the importance of education. This program is expected to become a sustainable model for increasing access to education for underprivileged children.